Effect of annealing temperature on dielectric properties of iron oxide prepared by sol–gel auto combustion method. Issue 1 (18th June 2021) - Yasnur, Sk; Maji, Prasenjit; Ray, Apurba; Mullick, Himadri; Das, Sachindranath
Abstract: In this study, different phases of iron oxide have been synthesized by sol–gel auto combustion route followed by annealing. Temperature and frequency-dependent dielectric properties have been studied in detail which provide the information on the contribution of grain and grain boundary in charge transport. Conductivity and electric modulus spectra have also been analyzed. The scaled coordination of impedance spectrum merges in a single master curve which signifies that the distribution of relaxation time is temperature independent. Complex impedance spectra have been used to evaluate activation energy ( Ea ) by using Arrhenius relation. The activation energy calculated for α-Fe2 O3 is 1.36 eV.